Experienced academy soccer coaches` perspectives on players` skilfulness - McCalman, W.; Goddard, S. G.; Fransen, J.; Crowley-McHattan, Z. J.; Bennett, K. J. M. (Science and Medicine in Football, 2024)
Introduction: Soccer coaches are critical to academies as they are central to identifying players with the potential to succeed (i.e., talent). Research suggests coaches perceive skill as determining players` potential. Regardless, researchers only broadly explored their views and quantified players` skill using objective measures, which is problematic as coaches still rely on their subjective intuition. A plausible reason is that skill assessments do not meet coaches` needs.